Redox - Khattak, Rozina (IntechOpen, 2020)
The book "Redox" provides vast insight into the oxidation-reduction reactions to its readers. The book consists of three sections that include redox in the coordination compounds, organic compounds and polymerization; redox in electrochemistry; and redox and fish welfare. The first section consists of three chapters that describe the role of redox reactions in several fields such as transition metal chemistry, degradation processes of toxic compounds and dyes in treatment of water and wastewater, the catalysis of oxidation of organic compounds by metal active sites, and synthesis of copolymers. The second section consists of two chapters. The role of redox reactions and reactivity description of compounds are discussed in the second section of the book. The non-aqueous redox flow batteries are described in this section. The third section extensively discusses the redox balance and fish welfare and consists of one chapter.